Changes in Oral Health-Related Behaviors and Oral Health of Children in Early Childhood during Social Isolation Caused by COVID-19 - Laís Canêdo Martins; Stefânia Werneck Procópio; Maisa Costa Tavares; Camila Faria Carrada; Flávia Almeida Ribeiro Scalioni; Saul Martins Paiva; Rosangela Almeida Ribeiro (Association of Support to Oral Health Research (APESB), 2024)
Objective: To assess changes in oral health-related behavior and oral health status in Brazilian children in early childhood perceived by their parents/caregivers during social isolation caused by COVID-19. Material and Methods: A cross-sectional study with parents/caregivers of children in southeastern Brazil aged 0-5 years who responded to an online questionnaire about sociodemographic data, dietary changes, oral hygiene, and oral health status of children during the COVID-19 pandemic. Results: Of the 119 parents/caregivers, 54.60% did not observe any changes in eating habits, and 81.50% maintained their children's oral hygiene. Associations were observed between the impact of the pandemic on the family income and changes in eating habits (p=0.02) and between lower family income and dental caries perceived by parents/caregivers (p=0.05). Z tests with Bonferroni correction showed that families with drastic income reduction were more likely to consume lower-cost foods (62.50%) than families with no impact or slight reduction on family income. Parents/caregivers did not identify dental caries (89.10%), toothache (92.40%), and dental trauma (92.40%) in their children. Conclusion: Parents/caregivers of children in southeastern Brazil aged 0-5 years observed behavioral changes in the dietary habits of families whose income was impacted by the pandemic, and their perception of dental caries was significantly associated with family income.